KARAKTERISTIK POTENSI WISATA ALAM PADA KAWASAN TAMAN WISATA ALAM SORONG - Matheus Beljai (AGRICOLA, 2017)
Nature Park Sorong (NPS) is one area of lowland tropical rain forest which has the characteristics of flora, fauna and natural scenery appealing as a potential major natural ecotourism. NPS natural landscape characteristics could be nature and artificial landscape such as: view of the river, view forestry, breeding and others. While the flora and fauna is quite diverse, and there are some endemic species. In its management regarding the promotion of natural tourism resources, the potential of this region is unknown as natural tourist area, so need early concepts as alternative development based on the characteristics of potential. Some initial alternative for nature tourism development in NPS seen by the characteristics of natural tourism potential and opportunities activities, required facilities and condition of forest communities and forest management.